Bending the Light: A Methodological Structure for Collaborative Theological Inquiry - Benac, Dustin; Kalbaugh, Juli; Coe, Hannah; Miller, Tatum; Moniz, Erin (Ecclesial Futures, 2023)
The shifting structure of religious life requires new research methodologies that can attend to the dynamic nature of faith and resource ongoing scholarship and religious practice. Rather than approaching research and resourcing as separate and iterative movements, a contextually-centered approach can engage and support religious scholarship and practice in dynamic religious climates. While existing methodologies have advanced research and practice in considerable ways, these developments now make possible an integrative approach that combines research, resourcing, and collaborative inquiry into a dynamic movement. This paper advances an argument through a theological fieldnote based on a year of collaborative research and resourcing completed by the Program for the Future Church (PFFC). Established in 2021, the PFFC is a research, resource, and relational hub that pilots solutions for emerging and pressing challenges before the Church. The methodology, “Bending the Light,” pursues collaborative action research by constituting three sites of inquiry: a Celebration, a Collaboratory, and a Contextual Research Hub. Nine practices guide individual and collective investigation(s): 1) identifying present gifts; 2) creating connections; 3) identifying commonalities; 4) clarifying presenting crises; 5) developing shared language; 6) elevating individual and collective imagination; 7) complexifying anchoring concepts; 8) exploring shared practice; and 9) piloting research and resources. Combining reflections from conveners and participants, this methodological structure enhances attention to the lived theologies that ground the life of faith and the forms of practice that can resource future research and Christian practice.